How I wonder what you are: Children's songs as a source of mental and internal state information. Issue 1 (25th August 2022) - Sudo, Mioko; Cheung, Zoe Ka Pui; Okada, Yasuko; Daniels, Jaxenne
Abstract: This study investigated (1) whether children's songs could be potential sources of internal state information and (2) cross‐cultural/linguistic differences in the availability of such information. We coded for expressions of mental states and other internal states in 255 English songs, likely accessed by children in the United States, and 255 Japanese songs, likely accessed by Japanese children. The majority of the songs in both samples contained at least one internal state expression, with songs containing four to five tokens and two types of internal state expressions on average. Japanese songs had more types of internal state expressions than English songs when comparing the two samples in proportion scores that controlled for the length of songs. However, differences between English and Japanese songs were negligible in the absolute frequency of tokens and types of internal state expressions, with the exception that Japanese songs were richer in ambiguous internal state expressions.